Digestion Performance and Microbial Metabolic Mechanism in Thermophilic and Mesophilic Anaerobic Digesters Exposed to Elevated Loadings of Organic Fraction of Municipal Solid Waste - Yiming Gao; Xiaoying Kong; Tao Xing; Yongming Sun; Yi Zhang; Xingjian Luo; Yong Sun (Energies, 2018)
Mesophilic and thermophilic anaerobic digestion reactors (MR and TR) for the organic fraction of municipal solid waste (OFMSW) were tested to reveal the differential microbial responses to increasing organic loading rate (OLR). MR exhibited faster adaptation and better performance at an OLR range of 1.0–2.5 g VS·L−1·d−1, with average profiles of a biogas yield of 0.38 L/gVSadded*d at 0.5 g/L*d OLR and 0.69 L/gVSadded*d at 2.5 g/L*d OLR, whereas TR had a biogas yield of 0.07 L/gVSadded*d at 0.5 g/L*d OLR and 0.44 L/gVSadded*d at 2.5 g/L*d OLR. The pyrosequencing results of amplicons revealed the microbial mechanisms of OFMSW anaerobic digestion. Larger shifts in the bacteria composition were observed in the TR with OLR elevation. For methanogens in both reactors, Methanothrix dominated in the MR while Methanosarcina was favored in the TR. Moreover, analysis of the mode and efficiency of metabolism between the MR and TR demonstrated different performances with more efficiency related to the limiting hydrolytic acid step.